Obesity in Schizophrenia - Mary V. Seeman (Journal of Obesity Management, 2016)
Over the last three decades, an epidemic of obesity has markedly affected patients suffering from mental illnesses such as schizophrenia. Antipsychotic medications used to treat schizophrenia are considered as major culprits. The aim of this review is to first consider risk factors, to then outline negative sequelae of obesity for this population, and finally to address timing and content of recommended clinical interventions. Medical databases were searched with the terms “”weight,” “obesity,” and “schizophrenia.” Selection of articles was guided by date of publication; recent papers are preferentially cited. The main findings were that, in addition to antipsychotic medications, socio-economics, lifestyle, immune factors, and circadian rhythms also contribute to obesity risk. A barrier to effective health promotion within psychiatry has been the concern that fears about gaining weight might stop individuals with schizophrenia from taking needed antipsychotic medication. Recommendations, therefore, are to keep the dose of antipsychotic medication as low as possible, avoid polypharmacy, encourage healthy eating and physical activity, address sleep problems and substance use, monitor weight, blood pressure, and metabolic parameters regularly, utilize motivational interviewing techniques and peer support, pay special attention to special needs such as those of women during pregnancy, and include bariatric surgery as a potential intervention. Conclusion: Besides careful attention to medication regimens, the literature supports the active encouragement and support of patient self-management strategies to both prevent and manage obesity in schizophrenia.
Keywords: Obesity